LINGUISTIC FEATURES OF THE CONCEPT OF UGLINESS IN HISTORICAL BOOKS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Jadidism movement has been started during the late 19 and early 20 century. It's objective to modify the world and to enter education in order to remove nostalgia through people. This article demonstrates the movement of jadidism , it's role, it's heroes and their work During jadidism period, a group of high statues man tried to eject jadid schoolers in order to become more and more powerful person in society. In one word this highlights how ugliness,both literal and metaphorical ,played a central role in Jadidism' s push for societal renewal. through article we analyzed the movement of jadidism by illustrating the book of 'Mehrobdan chayon' by Abdulla Avloniy